Avian Models in Teratology and Developmental Toxicology - Smith, Susan M. (Methods Mol Biol, 2012)
The avian embryo is a long-standing model for developmental biology research. It also has proven utility for toxicology research both in ovo and in explant culture. Like mammals, avian embryos have an allantois and their developmental pathways are highly conserved with those of mammals, thus avian models have biomedical relevance. Fertile eggs are inexpensive and the embryo develops rapidly, allowing for high throughput. The chick genome is sequenced and significant molecular resources are available for study including the ability for genetic manipulation. The absence of a placenta permits the direct study of an agent’s embryotoxic effects. Here we present protocols for using avian embryos in toxicology research including egg husbandry and hatch, toxicant delivery, and assessment of proliferation, apoptosis, and cardiac structure and function.